An animated music video of the song "Pagsarmingan" by Salidummay to depict the struggles and aspirations of indigenous people in the Cordillera - Marcelang, Ma. Oliana A.
The Cordillera region is home to several ethnolinguistic groups: the Tingguan, Isneg, Kalinga, Kankanaey, Ifugao, Bontok, and Ibaloi. Its fertile lands provide these communities with many sources of livelihood like farming, fishing, and small-scale mining. Due to the region's abundance in natural resources and the demand for renewable energy, the state as well as private corporations, saw its potential for development projects. These include hydro and geothermal power plants among other projects. Though these projects provide energy to a large population, it also managed to displace hundreds and thousands of indigenous people and communities who depend on the land. Their agricultural and ancestral lands were destroyed to make way for power plants and large-scale mining for the sake of national development despite heavy protests. The voice of the victims of these projects are often drowned out against the roar of progress and modernization; the benefit of the majority prevails over the welfare of those at the periphery. But through the Salidummay, a progressive music group from the Cordillera, the struggles of the indigenous people, the minorities, and the marginalized can be heard. The Salidummay music group's aim is to defend the land, life, and culture of the indigenous people through music. It is important to gain awareness that the Cordilleran struggle is not far from our own; their displacement, militarization, and destruction of environment for progress's sake, is all rooted to a systematic problem. Although the indigenous peoples have a different way of life and a cultural identity distinct from others, they are not separate from fellow Filipinos and we should be one in their struggle. To be one in their struggle, one must gain awareness of their situation. This has been accomplished by the Salidummay through their music. However, cultural differences such as language, as their songs are sung mostly in Ilokano, may serve as a hindrance to non-Ilokano speakers. Nevertheless, the language barrier wouldn't deter our understanding if communicated effectively through an engaging medium.